Seroprevalence of Wenzhou virus in China - Li Guo; Shasha Liu; Jingdong Song; Lianlian Han; Hu Zhang; Chao Wu; Conghui Wang; Hongli Zhou; Jianwei Wang (Elsevier, 2020)
Wenzhou virus (WENV) was first identified in rodents and Asian house shrews in Wenzhou, Zhejiang Province, China. However, little is known about the prevalence of WENV infections in humans in China. To determine the threat that WENV may pose to humans, we determine the seroprevalence of WENV in healthy individuals in China in this study. Cross-reactivities of nucleoprotein (NP) were detected between Lymphocytic choriomeningitis virus (LCMV) and WENV using Western blot and ELISA assy. The prevalence of specific IgG antibodies against WENV NP was investigated in different age groups of 830 healthy individuals aged 0-70 years old in China using a competition ELISA assay. The results indicate that WENV and LCMV share cross-reactive epitopes between NPs. The total seroprevalence of WENV in healthy adults was 4.6%, with 3.6% (8/221) for individuals 15-44 years of age, 5.4% (17/317) for individuals 45-59 years of age, and 4.1% (4/98) for older adults over 60. The total seroprevalence of WENV in children under age 15 was 1.5%, with 2.9% (1/34) in children aged 2-5 years, and 2.2% in 5-14 years (2/91). The finding suggests that WENV or WENV-like virus may sporadically infect humans of China.